Karl Marx and the British labour movement : years of the First International - Collins, Henry; Abramsky, Chimen (London : Macmillan & co, 1965)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Marx, Karl; Eerste Internationale (1864-1876).; arbeidersbeweging; Engeland